Co-Curricular Model Design in Overcoming Bullying Practices in Phase F Students in Senior High School - Wardi, Wardi; Hasbi, Hasbi; Iman RN, Bustanul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The ongoing prevalence of bullying among phase F students, which affects their psychological and learning processes, motivates this research. The purpose of this research is to develop a co-curricular model based on Islamic religious education in the form of additional learning manuals to reduce bullying behavior and foster positive character in students. This research uses the research and development method (Research and Development) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects are phase F students and Islamic Religious Education teachers, while the research object is in the form of co-curricular guidebook products. Data collection techniques include observation, interviews, questionnaires, and documentation, with qualitative and quantitative descriptive data analysis. The results of the study indicated that bullying practices in schools appeared in physical (hitting) and verbal (mocking and disruptive) forms. The co-curricular handbook products developed have undergone validity and practicality tests, yielding average results of 85.50% (very valid) and 87.50% (efficient), indicating that they are suitable for use. Thus, the development of an Islamic religious education-based co-curricular model can be an effective strategy for suppressing bullying practices while contributing to the formation of students' character and enriching Islamic educational literature.